2004
DOI: 10.1200/jco.2004.08.189
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Biologic End Points and Pharmacokinetics in Patients With Metastatic Breast Cancer After Treatment With Erlotinib, an Epidermal Growth Factor Receptor Tyrosine Kinase Inhibitor

Abstract: Erlotinib has inhibitory biologic effects on normal surrogate tissues and on an EGFR-positive tumor. The lack of reduced tumor proliferation may be attributed to the heterogeneous expression of receptor in the EGFR-positive patient and absence of target in this cohort of heavily pretreated patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
83
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(87 citation statements)
references
References 24 publications
4
83
0
Order By: Relevance
“…Thus the comparison of the PD parameters estimated from different models could be a reasonable approach to predict a clinical response. Tan et al suggested that for cancer patients who were treated with a effective daily dose of 150 mg erlotinib orally, the minimum steady-state concentration (C ss, min ) was 1.473 µg/mL (SD=0.877 µg/mL), the maximum steady-state concentration (C ss, max ) was 2.528 µg/mL (SD=1.187 µg/mL) and the average steady-state concentration (C ss, ave ) was 1.818 µg/mL (SD=0.973 µg/mL) [32] . For this research, the IC 50 for pEGFR degradation was 1.80 µg/mL, which was within the steady-state minimum and maximum concentration window.…”
Section: Discussionmentioning
confidence: 98%
“…Thus the comparison of the PD parameters estimated from different models could be a reasonable approach to predict a clinical response. Tan et al suggested that for cancer patients who were treated with a effective daily dose of 150 mg erlotinib orally, the minimum steady-state concentration (C ss, min ) was 1.473 µg/mL (SD=0.877 µg/mL), the maximum steady-state concentration (C ss, max ) was 2.528 µg/mL (SD=1.187 µg/mL) and the average steady-state concentration (C ss, ave ) was 1.818 µg/mL (SD=0.973 µg/mL) [32] . For this research, the IC 50 for pEGFR degradation was 1.80 µg/mL, which was within the steady-state minimum and maximum concentration window.…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, the clinical benefit observed with anti-EGFR tyrosine kinase inhibitors (TKIs) across different disease entities has been variable. For example, EGFR TKIs are largely inactive in colorectal cancer and breast cancer (Tan et al, 2004;Baselga and Arteaga, 2005). Nevertheless, two of these drugs, gefitinib and erlotinib, have demonstrated clinical activity in non small cell lung cancer and responses have been observed in patients with advanced pancreatic cancer and in head-and-neck cancer (Baselga, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It is approved for the treatment of advanced nonsmall cell lung cancer as a single agent and advanced pancreatic cancer in combination with gemcitabine. Erlotinib has an average oral bioavailability in humans of 59% (Frohna et al, 2006), but exhibits substantial (up to eight-fold) interindividual pharmacokinetic variability (Hidalgo et al, 2001;Tan et al, 2004), which may result in variable treatment outcomes. Erlotinib is extensively metabolised into multiple products , including an active O-desmethyl metabolite, OSI-420.…”
mentioning
confidence: 99%